Success management in information systems projects: a literature review - Takagi, Nilton Hideki (2019)
In a technological and increasingly complex environment, planning and managing information systems (IS) has become a necessity, and achieving success in IS projects a challenge. In order to characterize how managers are implementing the success management process and what are the particularities of the IS projects, a literature review was carried out. We have found around six hundred papers with evidence of activities related to success management. Only approximately 1% of these works have the description of a process or methodology to manage success in projects, and no recent references have been found focused on the area of IS.